Giúp mình với Giải phương trình a, căn ( x^2 + 6x + 9 ) = 3x – 6 b, căn ( x^2 – 4x +4 ) – 2x +5 =0 c, căn ( x-3 / 2x+1) = 2 d, 10x-7 / căn ( 3x+5)

Question

Giúp mình với
Giải phương trình
a, căn ( x^2 + 6x + 9 ) = 3x – 6
b, căn ( x^2 – 4x +4 ) – 2x +5 =0
c, căn ( x-3 / 2x+1) = 2
d, 10x-7 / căn ( 3x+5) = căn ( 3x+5)

in progress 0
Caroline 1 tháng 2021-08-07T18:31:27+00:00 2 Answers 3 views 0

Answers ( )

    0
    2021-08-07T18:32:48+00:00

    Đáp án:

    a) $\sqrt[]{x²+ 6x + 9}$ = 3x – 6 

    ⇔$\sqrt[]{(x+3)²}$ =3x – 6 

    ⇔x+3-3x+6=0

    ⇔-2x+9=0

    ⇔-2x=-9

    ⇔x=$\frac{9}{2}$ 

    vậy PT có nghiệm x=$\frac{9}{2}$ 

    b)$\sqrt[]{x²-4x+4}-2x+5$ =0

    ⇔$\sqrt[]{(x-2)²}-2x+5$=0

    ⇔x-2 -2x+5=0

    ⇔-x+3=0

    ⇔-x=-3

    ⇔x=3

    c)vs x≥3 , x<-1/2

    $\sqrt[]{\frac{x-3}{2x+1}}$ =2

    ⇔$\frac{x-3}{2x+1}$ =4

    ⇔x-3=4(2x+1)

    ⇔x-3=8x+4

    ⇔-7x=7

    ⇔x=-1(TM)

    d) vs x<-5/3 ta có

    $\frac{10x-7}{\sqrt[]{3x+5}}$ =$\sqrt[]{3x+5}$

    ⇔10x-7=$\sqrt[]{3x+5}$.$\sqrt[]{3x+5}$

    ⇔10x-7=$\sqrt[]{(3x+5)²}$

    ⇔10x-7=3x+5

    ⇔7x=12

    ⇔x=$\frac{12}{7}$ 

    Giải thích các bước giải:

     chúc bn hk tốt

    0
    2021-08-07T18:33:20+00:00

    Đáp án:

    d. \(x = \dfrac{{12}}{7}\)

    Giải thích các bước giải:

    \(\begin{array}{l}
    a.\sqrt {{x^2} + 6x + 9}  = 3x – 6\\
     \to {x^2} + 6x + 9 = 9{x^2} – 36x + 36\left( {DK:x \ge 2} \right)\\
     \to 8{x^2} – 42x + 27 = 0\\
     \to \left( {2x – 9} \right)\left( {4x – 3} \right) = 0\\
     \to \left[ \begin{array}{l}
    x = \dfrac{9}{2}\left( {TM} \right)\\
    x = \dfrac{3}{4}\left( l \right)
    \end{array} \right.\\
    b.\sqrt {{x^2} – 4x + 4}  = 2x – 5\\
     \to {x^2} – 4x + 4 = 4{x^2} – 20x + 25\left( {DK:x \ge \dfrac{5}{2}} \right)\\
     \to 3{x^2} – 16x + 21 = 0\\
     \to \left( {x – 3} \right)\left( {3x – 7} \right) = 0\\
     \to \left[ \begin{array}{l}
    x = 3\left( {TM} \right)\\
    x = \dfrac{7}{3}\left( l \right)
    \end{array} \right.\\
    c.DK:\left[ \begin{array}{l}
    x \ge 3\\
    x <  – \dfrac{1}{2}
    \end{array} \right.\\
    \sqrt {\dfrac{{x – 3}}{{2x + 1}}}  = 2\\
     \to \dfrac{{x – 3}}{{2x + 1}} = 4\\
     \to x – 3 = 8x + 4\\
     \to 7x =  – 7\\
     \to x =  – 1\left( {TM} \right)\\
    d.DK:x >  – \dfrac{5}{3}\\
    \dfrac{{10x – 7}}{{\sqrt {3x + 5} }} = \sqrt {3x + 5} \\
     \to 10x – 7 = 3x + 5\\
     \to 7x = 12\\
     \to x = \dfrac{{12}}{7}
    \end{array}\) 

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )